Optimal Subcarrier Allocation Algorithm for OFDMA Systems - Sahar Salman Mahmood (Engineering and Technology Journal, 2013)
An optimal subcarrier allocation algorithm is proposed for orthogonal frequency division multiple access systems over Rayleigh fading channels with channel state information feedback. The transmitted orthogonal frequency division multiple access frame is divided into groups called subchannels according to the detected number of users at the base station. The pilots are reduced for the stable subchannel and replaced with additional data subcarriers in order to increase the total system throughput. Simulation and semi-analytical results demonstrate that the throughput performance of the proposed method outperforms the conventional approaches